Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Strelitzia reginae Aiton (family Strelitziaceae), commonly known as bird of paradise and crane flower, is a perennial plant which is native to South Africa. The plant grows to 2 m tall, with large leaves to 70 cm long and 30 cm wide.The species produces showy flowers consisting of orange sepals and purple or blue petals and has been widely naturalised globally as an ornamental plant. However, S. reginae also is used in South African traditional medicine to treat diseases caused by bacterial pathogens, particularly urinary tract infections (UTI’s) and sexually transmitted infections (STI’s).1,2 Decoctions prepared from crushed S. reginae roots were considered particularly useful for the easing the symptoms of sexually transmitted diseases (including inflamed glands) in cultures from the Kwa Zulu-Natal region of South Africa, including the Zulus. A recent study screened a pan- el of South African plants with traditional uses in the treatment of STI’s and UTI’s for the ability to inhibit the pathogens Candida albicans (thrush), Gardnerella vaginalis (bacterial vaginosis), Neisseria gonorrhoeae (gonorrhea), Oligellaureolytica (bacterial vaginosis), Trichomonas vaginalis (tricho- moniasis), and Ureaplasma urealyticum (bacterial vaginosis).3 That study reported S. reginae dichloromethane: methanol (1:1) extracts inhibited the growth of all of the pathogens screened. The extract was a particularly good inhibitor of O. ureolytica and T. vaginalis, with MIC values of 0.6 and 1 mg/mL respectively. The extract was also a moderate inhibitor of C. albicans (2 mg/mL), G. vaginalis (3 mg/mL), Neisseria gonorrhoeae (2 mg/mL) and U. urealyticum (2 mg/mL). Interestingly, aqueous extracts (the form in which the plant is traditionally used) were generally substantially less po- tent, with MIC values up to 8 times higher than for the solvent extraction. This photograph was taken in Brisbane, Australia in 2016 by Dr Ian Cock.